2011
DOI: 10.4319/lo.2011.56.2.0540
|View full text |Cite
|
Sign up to set email alerts
|

Linking diel patterns in community respiration to bacterioplankton in an oligotrophic high‐elevation lake

Abstract: We examined the role of heterotrophic bacterioplankton in structuring diel patterns in community respiration (CR) in an oligotrophic alpine lake. We used continuous measurements of dissolved oxygen from both free-water and in situ incubation chambers to characterize a consistent diel pattern in oxygen drawdown with two distinct phases. CR rates averaged 15.4 times higher during the late afternoon to early night phase, which lasted for up to 5 h past dusk before rapidly transitioning to the lower rate phase, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 49 publications
4
47
0
1
Order By: Relevance
“…Bacterial abundance has been shown to be a seasonal driver of NEP within the epilimnion of Emerald Lake (Sadro 2011) and is likely a driver of variation in NEP with depth as well. Although not measured in this study, bacterioplankton abundance is known to increase with increasing depth and Chl a concentration in Emerald Lake (Nelson 2008), a pattern of covariation that is also found in other lakes (Pace and Cole 1994), sometimes in response to the higher phytoplankton biomass of deep chlorophyll maxima (Cole et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial abundance has been shown to be a seasonal driver of NEP within the epilimnion of Emerald Lake (Sadro 2011) and is likely a driver of variation in NEP with depth as well. Although not measured in this study, bacterioplankton abundance is known to increase with increasing depth and Chl a concentration in Emerald Lake (Nelson 2008), a pattern of covariation that is also found in other lakes (Pace and Cole 1994), sometimes in response to the higher phytoplankton biomass of deep chlorophyll maxima (Cole et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Petrucio and Barbosa (2004) demonstrated that bacterioplankton production may vary widely over the course of the day even in tropical lakes. On the other hand, Sadro et al (2011) reported higher respiration rates occurring at dusk and in the first part of the night, coupled directly to the diel production of organic carbon. Although changes in temporal patterns have been studied for several decades, much less is known about the diel changes in aquatic metabolism (Staehr and Sand-Jensen 2007;Marotta et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, heterothrophic organisms, especially bacteria, are expected to contribute to CRR higher than OCR because their metabolism is expected to be enhanced by the primary production taking place simultaneously (Pringault et al 2007(Pringault et al , 2009Sadro et al 2011). Hence, incubations in the lake, in which CRR was similar to OCR (Fig.…”
Section: Respiration In the Lightmentioning
confidence: 99%